2001
DOI: 10.1097/00000637-200104000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Microsurgical Ear Replantation Without Venous Repair: Failure of Development of Venous Channels Despite Patency of Arterial Anastomosis for 14 Days

Abstract: The authors describe a case of microvascular ear replantation with repair of the artery only and medicinal leech therapy that survived for 14 days but ultimately failed as a result of the absence of development of venous channels between the replant and the recipient bed. A 35-year-old man presented with complete avulsion of 80% of the right external ear. The auricle was revascularized successfully via transposition of the superficial temporal artery (STA) and end-to-end anastomosis between the STA and an iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 18 publications
0
34
0
Order By: Relevance
“…For the purpose of further analysis only cases of arterial and venous reconstruction (group 1 [ N = 38]) and artery‐only anastomosis (group 2 [ N = 19]) were included. The duration of surgery was reported in 23 cases in group 1 and 9 cases in group 2 with the median duration of surgery being 6 and 4 hour in group 1 and group 2, respectively ( P < 0.005; Table ).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…For the purpose of further analysis only cases of arterial and venous reconstruction (group 1 [ N = 38]) and artery‐only anastomosis (group 2 [ N = 19]) were included. The duration of surgery was reported in 23 cases in group 1 and 9 cases in group 2 with the median duration of surgery being 6 and 4 hour in group 1 and group 2, respectively ( P < 0.005; Table ).…”
Section: Resultsmentioning
confidence: 92%
“…As such, in the setting of adequate arterial inflow, one has to ensure venous drainage only until intrinsic drainage has been established. The importance of adequate debridement of the wound bed to facilitate neovascularization cannot be overstated …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Akyerek et al [1] have reported an unsuccessful replantation in spite of using medicinal leeches, but Jeng et al [5], Concannon and Puckett [2], Otto et al [10], and Talbi et al [11] describe complete healing of ears even in cases of venous insufficiency due to not suturing veins and use of leeches.…”
Section: Discussionmentioning
confidence: 99%
“…More often one can find reports on repairing the arterial system and the impossibility of repairing the veins. This is the reason why many authors have used medicinal leeches for venous drainage [1,2,10,11]. This situation is due partly to the contusion mechanism of amputations and partly to the small vessel size, which can be a limiting factor.…”
Section: Introductionmentioning
confidence: 99%